Cirugía oncológica radical en el anciano . - Herrero Payo, José A.; Llorente Abarca, C.; Páez Borda, A.; Sánchez Sánchez, E.; Berenguer Sánchez, A.; Acebal Lucía, J.; Bustamante Alarma, S. (Clínicas Urológicas de la Complutense, 1993)
Sin resumen